The Impact of Population Ageing on Public Finances in the EU-27: A Systematic Literature Review - María Cadaval-Sampedro; Santiago Lago-Peñas; Xoaquín Fernández-Leiceaga; Alejandro Domínguez-Lamela (Revista Galega de Economía, 2026)
Population ageing constitutes one of the most significant structural challenges for the long-term sustainability of public finances in the EU-27. This paper provides a systematic literature review (SLR) following PRISMA guidelines, complemented by a concise bibliometric analysis, of the fiscal consequences of demographic ageing. The review focuses on public revenues, public expenditure, fiscal sustainability, and institutional policy responses. The evidence shows that ageing affects both revenues and expenditures. It reduces labour-based tax bases through declining working-age populations, while increasing pressure on pensions, healthcare, and long-term care (LTC), particularly due to rising dependency at advanced ages. However, the fiscal impact of ageing is not uniform. It depends on the interaction between exogenous demographic trends and endogenous institutional factors, including labour-market participation, productivity, health status and the design of tax and welfare systems. As a result, similar demographic trajectories may generate different fiscal outcomes across countries. The literature highlights increasing uncertainty in healthcare and LTC expenditure, driven by technological change and morbidity patterns. Effective policy responses require coordinated reforms combining pensions, labour markets, taxation, and health systems, while political-economy constraints remain a key limitation.